Phase angle measured by bioelectrical impedance analysis in Polish College students. Preliminary observations - Małecka-Massalska, Teresa; Gołębiowski, Paweł; Chara, Krzysztof; Władysiuk, Magdalena; Smoleń, Agata; Lupa-Zatwarnicka, Krystyna (Polish Journal of Public Health, 2013)
Introduction. Phase angle (PA) is an indicator based on resistance (R) and reactance (Xc) received from bioelectrical impedance analysis (BIA). Although the biological significance of PA is still not clear, it appears to have an important prognostic role in nutrition state assessment. Aim. The study aimed to investigate the differences in resistance, reactance and phase angle in the group of Polish men and women. Material and methods. The whole-body analyses were made with ImpediMed bioimpedance analysis SFB7 BioImp v1.55 (Pinkeba Qld 4008, Australia) in the group of 30 women and 30 men – the students of Lublin University of Technology. Phase angle was calculated directly from body Xc and R (PA=arcus tangens Xc/R x 180 stopni/π). R and Xc were measured directly in ohms at 5, 50, 100 and 200 kHz. For group comparisons of metric data the t-Student test was used. The value of p<0.05 was considered statistically significant. Results. At 50 kHz there was no statistically significant difference between the male and female university students’ groups in reactance (59.63±6.46 ohm vs. 61.54±8.56 ohm, respectively; p=0.34). There was a statistically significant difference between the male and female university students’ group in resistance (595.46±62.84 ohm vs. 725.28±74.40 ohm, respectively; p<0.000001) and PA (5.75º±0.65 vs. 4.86º±0.53, respectively; p<0.000001). Conclusions. The evaluation of phase angle computed by resistance and reactance measurements by bioimpedance analysis differ in group of Polish university male and female students. Further observational research investigating these properties in larger groups would be welcomed to elucidate and/or confirm these findings.